2020
DOI: 10.1088/1361-6595/aba920
|View full text |Cite
|
Sign up to set email alerts
|

Tailored voltage waveforms applied to a capacitively coupled chlorine discharge

Abstract: Tailored voltage waveform, composed of a fundamental frequency and the second harmonic, is applied to a capacitively coupled chlorine discharge operated in the pressure range 1–50 Pa. The electronegativity is very high and the electron power absorption is mainly due to drift-ambipolar (DA) electron power absorption within the electronegative core. For operating pressures of 1 and 10 Pa the creation of a dc self-bias and asymmetric response is demonstrated and applied to control the ion bombardment energy while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 67 publications
3
32
1
Order By: Relevance
“…Besides, by increasing gas pressure, Liu et al and Wen et al [13,33] reported the α to γ mode transition in Ar, whereas, the heating mode transited from the α to a combination of the α and DA mode, and finally into the DA mode in CF 4 [17]. When the ion plasma frequency becomes comparable to or higher than the driving frequency, a transition to the STR mode at high pressures was experimentally observed in CF 4 [34], and the similar conclusion has been obtained in Cl 2 gases [28] by simulation.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Besides, by increasing gas pressure, Liu et al and Wen et al [13,33] reported the α to γ mode transition in Ar, whereas, the heating mode transited from the α to a combination of the α and DA mode, and finally into the DA mode in CF 4 [17]. When the ion plasma frequency becomes comparable to or higher than the driving frequency, a transition to the STR mode at high pressures was experimentally observed in CF 4 [34], and the similar conclusion has been obtained in Cl 2 gases [28] by simulation.…”
Section: Introductionsupporting
confidence: 58%
“…In electropositive gases, such as Ar, He and Ne, the discharge is either in the α mode or/and the γ mode [10,15,24,25]. By contrast, in electronegative plasmas, such as CF 4 , O 2 , SF 6 , SiH 4 , Cl 2 , the discharges may also work in the DA mode or/and the STR mode [26][27][28][29][30][31]. Through a combination of numerical simulation and experimental analysis, Donko et al [32] studied the effect of the gas mixture ratio in Ar/CF 4 discharges, and they confirmed that when the proportion of Ar was relatively high, the discharge changed from the DA to the α mode, or even the γ mode if the secondary electron emission (SEE) coefficient is high enough.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the coupling effect has also been observed in traditional dual frequency (DF) capacitively coupled plasmas (CCPs) [22][23][24][25][26][27][28][29][30]. Therefore, the electrically asymmetric discharge, which is driven by a fundamental frequency and its second harmonic, has been proposed to ideally realize the separate control of the ion flux and ion energy on the substrate [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Heil et al [31] first revealed that a DC self-bias was generated due to the discharge asymmetry, and it almost changed linearly with the phase shift between the two frequencies, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The spatio-temporal distributions of the electron power absorption and the ionization within the radiofrequency (RF) period determine the operation mode of the discharge. In low-pressure CCPs, several different discharge operation modes can be identified: the α-mode and the γ-mode [6] are typical in electropositive gases, while the driftambipolar (DA) mode [7] and the striation (STR) mode [8][9][10][11][12] can be observed in electronegative gases. In the α-mode, the ionization, caused by energetic electrons accelerated by electric fields during the times of sheath expansion, is concentrated at the bulk side of the expanding sheath edge, while in the γ-mode, the ionization, dominated by secondary electrons (SEs) accelerated by the strong electric field inside the sheaths, is concentrated within the sheath region.…”
Section: Introductionmentioning
confidence: 99%